Pemberdayaan Agropreneur Muda Melalui Pelatihan Budidaya Ikan Lele Kolam Mini Di SMP Sumbarrang Kabupaten Gowa - Muhammad Aldair Mukstofa Carda; Zakiah; Mustaqiim Pangestu; Syahnan Aly Lubis; Nur Islah Sugianto (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
This community service program was conducted to enhance the entrepreneurial capacity of junior high school students by strengthening their technical literacy in catfish aquaculture, a fisheries commodity with substantial economic value. The activity was implemented from 3–7 November 2025 at SMP Sumbarrang, Gowa Regency, and was delivered in a theoretical format due to limited facilities for practical aquaculture activities. The training materials covered the concept of youth agropreneurship, household-scale catfish farming techniques, feed management, community-based marketing strategies within the school environment, business feasibility analysis, and the development of entrepreneurial action plans. The methods employed included interactive lectures, group discussions, business plan simulations, and pre–post test evaluations. The results indicated a significant improvement in students’ technical literacy, reflected by a 49–50% increase in understanding related to farming techniques, feed management, and market opportunities. Entrepreneurial motivation also increased among 78% of participants, demonstrated by greater willingness to express business ideas and heightened awareness of their family’s economic potential. Support from schools and parents was identified as a key factor strengthening the sustainability of the program. Overall, this activity produced a replicable empowerment model for cultivating young agropreneurs in rural school settings, contributing to local economic development through the fisheries sector.